PERBANDINGAN HASIL CITRA ANATOMI ANTARA CT SCAN ABDOMEN PRE KONTRAS DAN VIRTUAL NON CONTRAST DENGAN PENYESUAIAN WINDOW WIDTH DAN CENTER MENGGUNAKAN DUAL ENERGY CT SCAN DI RS BHAYANGKARA - RORY AGUSTRIA; TRI SUWARTINI (Jurnal Kesehatan Pertiwi, 2023)
The results comparison between anatomical image of abdominal pre contrast CT Scan and virtual non contras with adjusment window width and center using Dual Energy CT Scan at Bhayangkara Hospital. The research purpose is to know the different image resulting in abdominal CT Scan using multislice CT and dual energy. The research had been done based on the method of analytical description and data collection obtained through direct observations from the beginning to the end of the examinations. From the statistical results using T test, it has been found the different image on both techniques.